Ambiguous Citizenship in an Age of Global Migration - Ní Mhurchú, Aoileann (Book collections on Project MUSE., 2014)
Citizenship is widely understood in binary statist terms: inclusion/exclusion, past/present, with the emphasis on how globalization brings such binaries into focus and exacerbates them. This book highlights the limitations of these positions and of current debate, and explores the possibility that citizenship is being reconfigured in contemporary political life beyond binary state oriented categories.